Ecological Heterogeneity of Oxbow and Floodplain Lakes Along the Kapuas Riverine System. Issue 1 (1st July 2022) - Subehi, L; Uno, H; Imroatushshoolikhah,; Sulastri,; Yustiawati,; Toruan, R L; Ajie, G S; Jasalesmana, T; Dianto, A; Afandi, A Y; Sulawesty, F; Julzarika, A; et al.
Abstract: Kapuas River in West Kalimantan with over 1, 143 km is the largest river in Indonesia. It serves as a main refuge for high potential biodiversity. Oxbow lakes along the Kapuas River are of high ecological essential due to the number and the diversity of habitats they provide. In addition, oxbow lakes are critical components of the floodplain systems of lowland rivers. The objective of this study was to explore the diversity of oxbow lakes and their connectivity to the main river. We conducted fieldwork to measure water quality and ecological components at 12 oxbow lakes along the Kapuas River and two lakes in the Sentarum complex in January - February 2020. We measured the environmental parameters including water depth, water temperature, Secchi/transparency, pH, dissolved oxygen concentration, chlorophyll-a concentration, total nitrogen, and total phosphorus concentrations. Aquatic biota, including phytoplankton and zooplankton community structures, were also observed at 12 oxbow lakes along the Kapuas River and two lakes in the Sentraum complex. The sampling points represented both permanent and non-permanent connectivity of the oxbow lakes to the main river. The result indicates the variability of environmental characteristics between the lakes, based on water quality and biota analysis; for example, water acidity, as indicated by pH, was likely to seem like the main variable determining the oxbow lake biota. Also, the habitat connectivity of oxbow lakes to the main river has significantly influenced the biotic composition.